2019
DOI: 10.7251/emc1802300m
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Managing the Urban Mobility Planning Process / Model Upravljanja Procesom Planiranja Urbane Mobilnosti

Abstract: The subject of research in this paper is the planning of urban mobility development in the narrow part of Sarajevo using a model based on the growth matrix. The hypothesis of this research is: Based on the analysis of supply and demand of the city traffic system, good practices in sustainable urban mobility and existing strategies and development plans, a model for managing the whole planning process of sustainable urban mobility of the city traffic system in Sarajevo by 2026 can be proposed.In accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After the verifications were done, i.e., the graphiological expertise 26 performed by the relevant bodies of the Ministry of Interior, it was concluded that the receipts contain forged signatures, which in fact proves that the pension money was appropriated by the clerk who distributed the pensions. 27…”
Section: An Example From Practical Experience Where Partial Forgery I...mentioning
confidence: 99%
“…After the verifications were done, i.e., the graphiological expertise 26 performed by the relevant bodies of the Ministry of Interior, it was concluded that the receipts contain forged signatures, which in fact proves that the pension money was appropriated by the clerk who distributed the pensions. 27…”
Section: An Example From Practical Experience Where Partial Forgery I...mentioning
confidence: 99%